2015
DOI: 10.1021/acs.langmuir.5b00815
|View full text |Cite
|
Sign up to set email alerts
|

Role of Flagella in Adhesion of Escherichia coli to Abiotic Surfaces

Abstract: The Harvard community has made this article openly available. Please share how this access benefits you. Your story matters. Abstract: Understanding the interfacial activity of bacteria is of critical importance due to the huge economic and public health implications associated with surface fouling and biofilm formation. The complexity of the process and difficulties of predicting microbial adhesion to novel materials demand study of the properties of specific bacterial surface features and their potential con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
110
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(115 citation statements)
references
References 67 publications
(137 reference statements)
5
110
0
Order By: Relevance
“…This transition can be associated with a change in cellular phenotype. For instance, when motile bacteria, such as Escherichia coli, adhere to a substratum (33,82,83), motility ceases, cell multiplication continues (84)(85)(86)(87), and early biofilm-related genes are upregulated, including those that encode additional adhesins (88)(89)(90). Although Karatan and Watnick (91) suggested that bacteria at this point can form either an adherent monolayer biofilm or a multilayer biofilm, the former is not sufficient to encompass some of the main characteristics of a complex biofilm, most notably the formation of ECM and a three-dimensional, controlled microenvironment that facilitates biofilm growth, nutrient acquisition, control of gas and pH, and cell-cell signaling (92)(93)(94)(95)(96)(97).…”
Section: Defining a C Albicans Biofilm: Lessons From Bacteriamentioning
confidence: 99%
“…This transition can be associated with a change in cellular phenotype. For instance, when motile bacteria, such as Escherichia coli, adhere to a substratum (33,82,83), motility ceases, cell multiplication continues (84)(85)(86)(87), and early biofilm-related genes are upregulated, including those that encode additional adhesins (88)(89)(90). Although Karatan and Watnick (91) suggested that bacteria at this point can form either an adherent monolayer biofilm or a multilayer biofilm, the former is not sufficient to encompass some of the main characteristics of a complex biofilm, most notably the formation of ECM and a three-dimensional, controlled microenvironment that facilitates biofilm growth, nutrient acquisition, control of gas and pH, and cell-cell signaling (92)(93)(94)(95)(96)(97).…”
Section: Defining a C Albicans Biofilm: Lessons From Bacteriamentioning
confidence: 99%
“…[13] For flagellated species such as E. coli and P. aeruginosa, flagella can play an additional role in both reversible and irreversible attachment on solid surfaces. [14][15][16] In nearly all cases, however, bacteria that interact with a solid will either irreversibly attach to a surface and begin producing extracellular polymeric substances (EPS) to eventually form a biofilm, or they will leave the surface and return to the planktonic state. [17] The shear stress created by flow conditions has been shown to enhance bacterial cell attachment to surfaces for a number of different species in a variety of ways, including the activation of catch-bonds in E. coli [18] and increasing the surface residence time of P. aeruginosa.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that E. coli H48 flagella are generally attracted to hydrophobic surfaces and are ten times more likely than the bacterial cell body to make contact with artificial surfaces. These collisions by flagella with hydrophobic abiotic surfaces are known to slow bacteria down, promoting adhesion (39,40). This is also true in near surface swimming, a biophysical process dependent on rotating flagella, which has been shown to aid cooperative colonisation by probing and facilitating docking at membrane protrusions (41,42).…”
Section: Discussionmentioning
confidence: 98%